Individual patient data meta-analysis of FMISO and FAZA hypoxia PET scans from head and neck cancer patients undergoing definitive radio-chemotherapy - Zschaeck, Sebastian; Löck, Steffen; Hofheinz, Frank; Zips, Daniel; Saksø Mortensen, Lise; Zöphel, Klaus; Troost, Esther G. C.; Boeke, Simon; Saksø, Mette; Mönnich, David; Seidlitz, Annekatrin; Johansen, Jørgen; et al. (Radiotherapy and oncology, 2020)
Background and purpose - Tumor hypoxia plays an important role in head and neck squamous cell carcinomas (HNSCC). Various positron emission tomography (PET) tracers promise non-invasive assessment of tumor hypoxia. So far, the applicability of hypoxia PET is hampered by monocentric imaging trials with few patients. - Materials and methods - Multicenter individual patient data based meta-analysis of the original PET data from four prospective imaging trials was performed. All patients had localized disease and were treated with curatively intended radio(-chemo)therapy. Hypoxia PET imaging was performed with 18F-Fluoromisonidazole (FMISO, 102 patients) or 18F-Fluoroazomycin-arabinoside (FAZA, 51 patients). Impact of hypoxia PET parameters on loco-regional control (LRC) and overall survival (OS) was analyzed by uni- and multivariable Cox regression. - Results - Baseline characteristics between participating centers differed significantly, especially regarding T stage (p < 0.001), tumor volume (p < 0.001) and p16 status (p = 0.009). The commonly used hypoxia parameters, maximal tumor-to-muscle ratio (TMRmax) and hypoxic volume with 1.6 threshold (HV1.6), showed a strong association with LRC (p = 0.001) and OS (p < 0.001). These findings were irrespective of the radiotracer and the same cut-off values could be applied for FMISO and FAZA (TMRmax > 2.0 or HV1.6 > 1.5 ml). The effect size of TMRmax was similar for subgroups of patients defined by radiotracer, p16 status and FDG-PET parameters for LRC and OS, respectively. - Conclusion - PET measured hypoxia is robust and has a strong impact on LRC and OS in HNSCC. The most commonly investigated tracers FMISO and FAZA can probably be used equivalently in multicenter trials. Optimal strategies to improve the dismal outcome of hypoxic tumors remain elusive.
Gesehen am 29.09.2020